Treatment of Primary Dysmenorrhea Affecting Menstruating Women Using Herbs: A Review - Por, Choo S.; Rajagopal, Mogana Sundari; Akowuah, Gabriel Akyirem; Chinnappan, Sasikala; Abdullah, Nor Hayati (Natural Products Journal, The, 2022)
Primary dysmenorrhea is a common condition that affects menstruating women, especially young women. Painful cramping in the lower abdominal area, nausea, vomiting, headache, and fatigue is associated with primary dysmenorrhea, which restricts women from normal living life. The productivity and work performance of women are heavily affected by the symptoms of primary dysmenorrhea. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and Low Dose Oral Contraceptive Pills (OCPs) are commonly prescribed for the treatment of primary dysmenorrhea. However, variability in individual response to the drugs and their side effects hinder their long-term use among women. Complementary medicine such as herbs is a promising alternative for the treatment of primary dysmenorrhea, but it lacks scientific evidence. The pharmacological and clinical studies of 9 herbs were included in this review. Although excellent analgesic effects of herbs were reported by clinical studies, the detailed mechanism of action of most herbs remains unelucidated. Several studies discovered that herbs exert analgesic effects through direct uterine muscle relaxation effect, inhibition of Cyclooxygenase- 2 (COX-2), inhibition of intracellular calcium level, and reduction of prostaglandin synthesis. Further investigation of pharmacological action and the recommended dosages of the herbs for the optimal analgesic effect is needed.
Keywords: pharmacological studies